PENGARUH PENGALAMAN AUDITOR, KOMPLEKSITAS AUDIT, DAN TEKANAN ANGGARAN WAKTU TERHADAP KUALITAS AUDIT DENGAN VARIABEL MODERATING PEMAHAMAN TERHADAP SISTEM INFORMASI (Studi Empiris pada Kantor Akuntan Publik di Pekanbaru, Medan dan Padang) - Alex B. Akbar Sitompul; M Rasuli; Devi Safitri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
In the face of competition between firms issue that increasing and accompanied by many problems faced by companies in Indonesia, company managers require the services of an accountant, in particular public accounting firm whose duties carry out audit of the financial statements. What has been presented in accordance PABU (Prinsip Akuntansi Berterima Umum) that is SAK (Standar Akuntansi Keuangan). Then, the influence of independent variables which include the complexity of the audit, the auditor's experience, time budget pressure, audit quality and understanding against information systems particularly in Kantor Akuntan Publik (KAP) Medan, Padang, Pekanbaru. From some of these variables, it can be concluded that all the variables affects the quality audit so that the auditor should be prepared with some of these variables so that the quality of audit in accordance with wishes of the client and the auditor.Keywords: auditor, experience, complexity, time and systems